Lid material
A lid material with a heat-sealing layer of ethylene-methyl acrylate-maleic anhydride copolymer addresses the sealing inadequacies for glass containers, ensuring robust adhesion and minimal residue, enhancing user comfort.
Patent Information
- Application Number
- JP2023112667
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
AI Technical Summary
Existing lid materials with heat sealing agents have insufficient sealing properties for glass containers, leading to difficulty in peeling and residue of the heat sealing agent on the glass container side, causing discomfort during use.
A lid material with a specific layer structure containing 20 to 80% ethylene-methyl acrylate-maleic anhydride copolymer in the heat-sealing layer, combined with other resins and additives, providing high sealing properties and minimal residue on glass containers.
The lid material achieves strong sealing for glass containers while minimizing the amount of heat sealing agent left behind when peeled off, ensuring a clean and comfortable usage experience.
Smart Images

Figure 2025009572000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a novel closure material. More specifically, the present invention relates to a closure material used to close containers, particularly glass containers. [Background technology]
[0002] Lids have been used to seal containers for storing food, medicines, etc. Lids include various types such as seal-type lids with a sealant layer, crown caps, screw caps, paper caps, etc. Among these, seal-type lids are particularly often used because they are inexpensive to manufacture, easy to seal, and easy to add anti-adhesion functions, printing, etc.
[0003] Known examples of such seal-type lid materials include those with a multi-layer structure that uses a heat seal agent that has high sealing properties for paper containers, plastic containers, etc. For example, a lid that uses a heat seal agent containing an ethylene methyl acrylate copolymer, an ethylene vinyl acetate copolymer, and polyamide wax has been disclosed (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special table 2005-505476 publication Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the lid material as described in Patent Document 1 has good sealing and peeling properties for paper or plastic containers, it has insufficient sealing properties for glass containers, and a satisfactory sealed state may not be obtained. In this case, if an attempt is made to improve the sealing properties, not only will peeling become difficult, but some of the heat sealant will remain on the glass container when it is opened, which may cause discomfort when eating or drinking by directly putting the glass container (e.g., a bottle) to the mouth.
[0006] Therefore, a main object of the present invention is to provide a lid material which has high sealing properties even when applied to glass containers, and which is less likely to leave a portion of the heat sealant on the glass container when peeled off. [Means for solving the problem]
[0007] As a result of extensive research into the problems of the prior art, the present inventors have found that a covering material having a specific layer structure can achieve the above object, thereby completing the present invention.
[0008] That is, the present invention relates to the following lid material. 1. A lid material comprising a substrate and a heat seal layer on at least one surface of the substrate, the heat seal layer containing 20 to 80% by weight of an ethylene-methyl acrylate-maleic anhydride copolymer. 2. The covering material according to item 1, wherein the heat seal layer further comprises at least one resin selected from the group consisting of polyolefin resins, polyester resins, ethylene vinyl oxide, ethylene vinyl alcohol copolymer resins, and ethylene vinyl acetate copolymers. 3. The covering material according to item 1, wherein the thickness of the substrate is 7 to 30 μm. 4. The amount of heat seal layer laminated is 10 to 30 g / cm2 in dry weight. 2 2. The covering material according to claim 1, 5. The covering material according to any one of items 1 to 4, which is used to heat-seal and hermetically seal a container having at least a glass opening by bringing the heat-seal layer into contact with the glass opening. Effect of the Invention
[0009] According to the present invention, it is possible to provide a lid material that has high sealing properties for a container and is less likely to leave a portion of the heat sealant on the container when peeled off.
[0010] In particular, in the present invention, since a specific amount of ethylene-methyl acrylate-maleic anhydride copolymer is contained in the heat seal layer, excellent sealing properties can be exhibited, particularly for glass containers, while the heat seal component is less likely to remain on the glass container when the lid material is peeled off from the container. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a diagram showing the basic layer structure of a covering material of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing the chemical structure of an ethylene-methyl acrylate-maleic anhydride copolymer. [Diagram 3] Schematic diagrams showing the chemical structures of ethylene-methyl acrylate copolymer (EMA, FIG. 3(a)), ethylene-ethyl acrylate copolymer (EEA, FIG. 3(b)), and ethylene-acrylic acid copolymer (EMA, FIG. 3(c)). [Figure 4] 1 is a schematic diagram showing a state in which a container opening is sealed with a lid material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] 1.Lid material The covering material of the present invention is a covering material comprising a substrate and a heat seal layer on at least one surface of the substrate, and is characterized in that the heat seal layer contains 20 to 80% by weight of an ethylene-methyl acrylate-maleic anhydride copolymer.
[0013] The covering material of the present invention has a base material (base material film) and a heat seal layer, and is basically configured such that the heat seal layer is directly laminated on at least one surface of the base material. For example, as shown in FIG. 1, a configuration in which a heat seal layer is provided on one surface of the base material can be adopted. In this case, since the heat seal layer is used to close the container opening, it is sufficient that it is formed at least in the area in contact with the container opening, and therefore the heat seal layer may be formed on the entire surface of the base material. In the following, each layer constituting the covering material of the present invention will be described.
[0014] Base material In the present invention, the substrate functions as a core material for the lid material, in particular by imparting stiffness to the lid material, imparting durability to the lid material against breakage, etc., and by providing strength to the lid material so that the lid material will not be accidentally broken when peeled off from the glass container.
[0015] Furthermore, in cases where it is undesirable for the contents filled in the container to be exposed to light, air, etc., the base material can be given a function to suppress the transmission of light, a function to prevent the intrusion of outside air, or a function to suppress the transmission of gas, such as preventing the smell of the contents from leaking out of the container.
[0016] The material of the substrate is not particularly limited as long as it has the above-mentioned functions, and various materials such as plastics, rubber, metal, glass, ceramics, paper, etc. can be used. Therefore, as a material for forming the substrate, for example, paper, synthetic paper, resin film, resin film with a vapor deposition layer, synthetic resin plate, aluminum foil or other metal foil, metal plate, woven fabric, nonwoven fabric, leather, synthetic leather, wood, glass plate, etc., alone or composite materials or laminate materials thereof can be suitably used. Among these, it is preferable to use aluminum foil or resin film with a vapor deposition layer, since it is possible to obtain a predetermined strength while preventing the transmission of light or gas.
[0017] The substrate may be a single layer or a multi-layer. The lamination method when using a multi-layer substrate is not limited, and known methods such as dry lamination, extrusion lamination, wet lamination, and heat lamination can be adopted. In addition, in the case of a multi-layer substrate such as a resin film with a deposition layer, the deposition layer can be formed by a method including a step of heating and evaporating the metal component (aluminum, etc.) to be deposited in a vacuum state and attaching the vapor to the surface of the resin film.
[0018] The substrate may usually be in the form of a film or sheet. In this case, the thickness (total thickness when the substrate is multi-layered) is not particularly limited, but is usually about 7 to 30 μm, and preferably 12 to 20 μm.
[0019] Heat seal layer In the lid material of the present invention, a heat seal layer is laminated on at least one surface of the base material. The heat seal layer is thermally bonded to the opening of the container, so that the lid material of the present invention can seal the container. That is, the surface of the lid material of the present invention that has the heat seal layer is heat sealed in contact with the glass container, and the glass container is covered and sealed.
[0020] The heat seal layer contains 20 to 80% by weight, preferably 40 to 80% by weight, and more preferably 60 to 80% by weight of ethylene-methyl acrylate-maleic anhydride copolymer. Therefore, for example, it can be set to 70 to 80% by weight. By setting the content in this range, it is possible to reliably obtain the effect that the heat seal agent is unlikely to remain on the container side when the lid material is peeled off from the container while having high sealing properties even for containers (particularly glass containers). If the content is less than 20% by weight, the sealing properties are weak and the lid material may peel off unintentionally. If the content exceeds 80% by weight, blocking may occur in part when heat-sealed to the container, making it impossible to seal the container.
[0021] Furthermore, as described above, in the covering material of the present invention, the content of ethylene-methyl acrylate-maleic anhydride copolymer is 40 to 80% by weight, which is desirable in that high sealing properties and peelability can be obtained regardless of the heat sealing temperature.
[0022] Here, ethylene-methyl acrylate-maleic anhydride copolymer (hereinafter sometimes abbreviated as "ET") has a structure as shown in Figure 2, in which methyl acrylate (part indicated by circle in Figure 2) and maleic anhydride (part indicated by triangle in Figure 2) are randomly copolymerized within the methylene chains of a polyethylene skeleton (a repeating structure of -(CH2-CH2)-). Ethylene-methyl acrylate-maleic anhydride copolymer has excellent thermal stability and excellent reactivity with OH groups, and has particularly good adhesion to glass containers. At the same time, because the amount of lamination (lamination thickness) is highly uniform, it is less likely that part of the heat sealant will remain on the glass container when the lid is peeled off from the glass container.
[0023] Ethylene-methyl acrylate-maleic anhydride copolymer is, as the name suggests, a copolymer containing three components: ethylene monomer, methyl acrylate (methyl acrylate) monomer, and maleic anhydride monomer.
[0024] In this case, the proportions of each monomer can be, for example, about 70 to 90% by weight of ethylene monomer, about 5 to 30% by weight of methyl acrylate monomer, and about 1 to 10% by weight of maleic anhydride monomer, but are not limited to these proportions as long as they do not impede the effects of the present invention.
[0025] As such an ethylene-methyl acrylate-maleic anhydride copolymer, known or commercially available products can be used. Also usable is an ethylene-methyl acrylate-maleic anhydride copolymer obtained by a known production method. Examples of commercially available products include those with the product names "Rexpearl ET220X", "Rexpearl ET220H", "Rexpearl ET230X", "Rexpearl ET330H", "Rexpearl ET350X", "Rexpearl ET530H", and "Rexpearl ET720X" (all manufactured by Japan Polyethylene Co., Ltd.).
[0026] In contrast, such effects cannot be obtained with ethylene-methyl acrylate copolymer (EMA, FIG. 3(a)), ethylene-ethyl acrylate copolymer (EEA, FIG. 3(b)), and ethylene-acrylic acid copolymer (EMA, FIG. 3(c)), which have structures similar to those of ethylene-methyl acrylate-maleic anhydride copolymer. However, these components may be contained within a range that does not impair the effects of the present invention.
[0027] The heat seal layer may contain components other than the ethylene-methyl acrylate-maleic anhydride copolymer as long as they do not impede the effects of the present invention. Examples of such components include resin components other than the ethylene-methyl acrylate-maleic anhydride copolymer (hereinafter also referred to as "second resin component"), filler particles, tackifiers, antiblocking agents, colorants, thickeners, and other various additives.
[0028] In particular, in the present invention, it is preferable that the heat seal layer contains a second resin component, and more preferably contains a thermoplastic resin. Examples of the thermoplastic resin include polyolefin resins such as polyethylene (PE) and polypropylene (PP), polyester resins such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT), and at least one of ethylene vinyl oxide (EVA), ethylene vinyl alcohol copolymer resin (EVOH), and ethylene vinyl acetate copolymer. Among these, polyolefin resins are preferable as the second resin component, and polyethylene (PE) is more preferable in terms of appropriate adhesiveness and peelability. The polyethylene may be any of low density polyethylene (LDPE), high density polyethylene (HDPE), linear low density polyethylene (LLDPE), and the like.
[0029] When the heat seal layer contains the second resin component, the content of the second resin component in the heat seal layer is not particularly limited and may be, for example, about 20 to 80% by weight, and preferably 20 to 60% by weight.
[0030] The amount of the heat seal layer to be laminated may be appropriately set depending on the desired heat seal strength, etc., and is not particularly limited. From the viewpoint of the balance between the seal strength and the peelability, it is preferably 10 to 30 g / cm2 in terms of dry weight. 2 The thickness of the heat seal layer may be determined according to the amount of lamination, and may be, for example, within the range of about 5 to 30 μm, but is not limited thereto.
[0031] Other layers In the present invention, if necessary, a layer used in a known lid material or the like may be formed on the surface of the substrate opposite to the surface having the heat seal layer. For example, at least one of an OP layer (overprint layer), a print layer, an adhesive layer, a surface protection layer, etc. may be used.
[0032] 2. Manufacturing method of the lid material The covering material of the present invention can be produced by a method including a step of forming a heat seal layer on one or both sides of a substrate.
[0033] Examples of this method include a) a step of laminating a preformed film for forming a heat seal layer (sealant film) onto a substrate, b) a step of co-extruding a raw material for the substrate and a resin composition for forming a heat seal layer while melting them, and c) a step of applying a coating liquid for forming a heat seal layer onto a substrate, etc. These steps can also be carried out using a known or commercially available device.
[0034] Among these, in the present invention, it is particularly desirable to adopt the above-mentioned step a) because it is possible to achieve a uniform thickness of the heat seal layer and, when the lid material is peeled off from the glass container, it is less likely that part of the heat sealant will remain on the glass container.
[0035] In the above step a), the film for forming the heat seal layer can be obtained by preparing a mixture containing each component as described above and then molding it into a film. The molding method is not particularly limited, and for example, any of melt extrusion molding methods (T-die method, inflation method), solution casting molding method, etc. can be adopted. In particular, in the present invention, as the melt extrusion molding method, a method of forming a film of the melt of the mixture on a resin film that can constitute one layer of the substrate can be preferably adopted.
[0036] In this case, the resin film may be any of the various resins used as substrates as described above, and polyolefin resin films may be preferably used. More specifically, a mixture containing 20 to 80% by weight of ethylene-methyl acrylate-maleic anhydride copolymer is heated to about 150 to 200°C and melted and applied to one side of a polyolefin resin film having a thickness of about 10 to 30 μm, and a film of the mixture is formed on the polyolefin resin film, thereby obtaining a film for forming a heat seal layer as a laminate of "substrate B / heat seal layer". This film can be used as the lid material of the present invention as it is, but in order to strengthen the function as a substrate, it is preferable to further laminate it with substrate A in the next step.
[0037] Next, a separately prepared substrate A and the substrate B side of the heat seal layer forming film are laminated using an adhesive as necessary to obtain a lid material including "substrate A / substrate B / heat seal layer". The adhesive used in this case is not particularly limited, and for example, a commercially available polyester adhesive or the like can be used. As the substrate A in this case, the above-mentioned examples can be adopted. For example, a laminate made of aluminum foil / PET is used as the substrate A, and the aluminum foil side is laminated with the substrate B side of the heat seal layer forming film, thereby suitably producing a lid material including the above-mentioned "substrate A / substrate B / heat seal layer" (i.e., "PET / Al foil / substrate B / heat seal layer").
[0038] 3. Use of lid material The lid material of the present invention can be used to seal various containers. In particular, since the heat seal layer of the lid material of the present invention has excellent adhesion to glass, it can be suitably used to seal at least a container including a glass opening by heat sealing the heat seal layer in contact with the glass opening.
[0039] An example of the use is shown in FIG. 4. FIG. 4 shows a cross-sectional view of a state in which the opening of a container 21 is sealed by the lid material 10 of the present invention. The container 21 has a flange 21a formed on the periphery of the opening. The flange 21a is substantially circular or polygonal when viewed from above. The heat seal layer 12 of the lid material 10 is abutted against the flange 21a surface and heat sealed, and the lid material 10 and the container 21 are joined via the heat seal area HS. This seals the inside space of the container 21, and protects the contents (not shown). Although the flange 21a is formed in the container in FIG. 4, the container may be flangeless or of other shapes as long as the specified heat seal can be performed.
[0040] In this case, even if at least the upper surface of the container opening (or flange 21a) is made of glass, the lid material of the present invention can be firmly attached, and even when the lid material is removed from the container when opening, it is possible to prevent or reduce the heat seal layer from remaining on the container side. Therefore, the lid material of the present invention can be suitably used as a lid material for glass containers (including glass bottles, etc.). In this case, the contents are not limited, and can include various products and goods such as food and beverages, medicines, cosmetics, and chemicals. EXAMPLES
[0041] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.
[0042] [Example 1] The substrate was a commercially available polyethylene terephthalate (PET) with a thickness of 12 μm, and a commercially available adhesive (polyester resin) was applied at a dry weight of 3 g / m 2 A 30 μm thick aluminum foil (1N30, manufactured by Toyo Aluminum Co., Ltd.) was laminated thereon to prepare a substrate. Next, as a heat seal layer, 80 wt% of ethylene-methyl acrylate-maleic anhydride copolymer (Rexpearl ET350X, manufactured by Japan Polyethylene Co., Ltd., hereinafter referred to as "ET") and 20 wt% of commercially available polyethylene (PE) were dry blended and extruded at 180°C to a thickness of 10 μm (10 g / cm in dry weight) on a 20 μm-thick polyethylene (PE) film. 2 A sealant film was prepared so that Next, a commercially available adhesive (polyester resin) was applied at a dry weight of 3 g / m2 on the surface of the above-mentioned substrate on which the aluminum foil was exposed. 2The polyethylene film side of the sealant film was then attached to the coated film. This resulted in a sample of a lid material of "PET / aluminum foil / PE / heat seal layer (ET80:PE20)" (the adhesive layer is omitted). Table 1 shows the composition of the heat seal layer (adhesive resin component) of this example, where "copolymer" indicates ET and "other" indicates a second resin component other than ET (the same applies to other examples and comparative examples below).
[0043] [Example 2] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ET50:PE50)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 50 wt% ethylene-methyl acrylate-maleic anhydride copolymer and 50 wt% polyethylene.
[0044] [Example 3] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ET40:PE60)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 40 wt% ethylene-methyl acrylate-maleic anhydride copolymer and 60 wt% polyethylene.
[0045] [Example 4] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ET20:PE80)" was obtained in the same manner as in Example 1, except that the heat seal layer contained 20 wt% ethylene-methyl acrylate-maleic anhydride copolymer and 80 wt% polyethylene.
[0046] [Comparative Example 1] A sample of a lid material of "PET / aluminum foil / PE / heat seal layer (EMA30:EVA50:PA5:PE15)" was obtained in the same manner as in Example 1, except that the heat seal layer consisted of 30 wt% ethylene-methyl acrylate copolymer (Rexpearl EMA, manufactured by Japan Polyethylene Corporation, hereinafter referred to as "EMA"), 50 wt% commercially available ethylene vinyl oxide (EVA), 5 wt% commercially available polyamide wax (PA), and the remainder 15 wt% polyethylene (PE).
[0047] [Comparative Example 2] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (EMA80:PE20)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 80 wt% ethylene-methyl acrylate copolymer (Rexpearl EMA, manufactured by Japan Polyethylene Corporation, hereinafter referred to as "EMA") and 20 wt% commercially available polyethylene (PE).
[0048] [Comparative Example 3] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (EEA80:PE20)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 80 wt% ethylene-ethyl acrylate copolymer (manufactured by Japan Polyethylene Corporation, Rexpearl EEA, hereinafter referred to as "EEA") and 20 wt% commercially available polyethylene (PE).
[0049] [Comparative Example 4] A sample of a lid material of "PET / aluminum foil / PE / heat seal layer (EAA80:PE20)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 80 wt% ethylene-acrylic acid copolymer (manufactured by Japan Polyethylene Corporation, Rexpearl EEA, hereinafter referred to as "EAA") and 20 wt% commercially available polyethylene (PE).
[0050] [Comparative Example 5] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ET10:PE90)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 10 wt% ethylene-methyl acrylate-maleic anhydride copolymer and 90 wt% polyethylene.
[0051] [Comparative Example 6] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ET90:PE10)" was obtained in the same manner as in Example 1, except that the heat seal layer was made of 10 wt% ethylene-methyl acrylate-maleic anhydride copolymer and 90 wt% polyethylene.
[0052] [Comparative Example 7] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (ionomer)" was obtained in the same manner as in Example 1, except that an ionomer in which the molecules of an ethylene-methacrylic acid copolymer are bonded with metal ions (Himilan 1652, manufactured by Dow-Mitsui Polychemicals Co., Ltd.) was used as the heat seal layer.
[0053] [Comparative Example 8] A sample of a lid material having a composition of "PET / aluminum foil / PE / heat seal layer (polyolefin)" was obtained in the same manner as in Example 1, except that a maleic anhydride-modified ethylene propylene random copolymer (Admer QE060, manufactured by Mitsui Chemicals) known as a polyolefin-based adhesive was used as the heat seal layer.
[0054] [Test Example 1] The lid materials obtained in each Example and Comparative Example were cut to 7 mm x 100 mm, and the heat seal layer was placed opposite a commercially available glass plate that resembled a glass container and heat sealed to bond them together. The heat seal conditions were: (a) low-temperature seal conditions at 140°C and 3 kg / cm 2 (b) 2 seconds at 240°C for high temperature sealing conditions and (c) 3 kg / cm 2 The experiment was conducted under two conditions: Next, the adhesive strength between the lid material and the glass plate bonded by heat sealing was measured. Specifically, a tensile tester (Strograph VE50D, Toyo Seiki Co., Ltd.) was used at room temperature (20°C), the edge of the lid material was peeled off slightly from the glass plate, the lid material was bent at 45°, and the laminated interface was peeled off at 45°, at a peeling speed of 100 mm / min and a chuck distance of 100 mm. The results are shown in Table 1. The peel strength (N / 15 mm width) referred to in this specification is obtained by measuring the peel strength of the above-mentioned strip-shaped sample having a sample width of 7 mm, and converting this value into the peel strength when the sample width is 15 mm (multiplied by 15 / 7). In addition, in Table 1, as an overall evaluation, sealability was evaluated as "good" when the seal strength was 5N / 15mm width or more, which is a necessary and sufficient seal strength, under both the low-temperature sealing condition and the high-temperature sealing condition, sealability was evaluated as "△" when it was below 5N / 15mm width under the low-temperature sealing condition but was 5N / 15mm width or more under the high-temperature sealing condition, and sealability was evaluated as "x" when it was below 5N / 15mm width under both the low-temperature sealing condition and the high-temperature sealing condition. Note that in Comparative Example 6 and Comparative Example 7, although the seal strength exceeded 5N / 15mm width under the high-temperature sealing condition, blocking occurred, so it was deemed that the glass container could not be sealed, and sealability was evaluated as "x".
[0055] [Test Example 2] A test for peelability of the lid material was carried out. In the above-mentioned Test Example 1, after peeling the lid material from the glass plate, the remaining state of the heat seal layer (heat seal agent) on the glass plate was visually observed. The results are shown in Table 1. When no part of the heat seal layer was visually confirmed to remain on the glass plate, the peelability was indicated as "good", and when the heat seal layer was visually confirmed to remain on the glass plate, the peelability was indicated as "poor". In addition, in the results of Test Examples 1 and 2, those that were all ◯ were given an overall rating of "◯", those that had a △ sealability but an ◯ peelability were given an overall rating of "△", and those that were × in at least either the sealability or the peelability were given an overall rating of "×".
[0056] [Table 1]
[0057] As is clear from the above results, the lid material of the present invention has high sealing properties even for glass containers, while heat seal components are unlikely to remain on the glass container side when peeled off. In particular, it is found that Examples 1 to 3, in which the heat seal layer contains 40 to 80% by weight of ET and 20 to 60% by weight of PE, have both higher sealing properties and good peelability.
Claims
1. A lid material comprising a substrate and a heat seal layer on at least one surface of the substrate, the heat seal layer comprising 20 to 80% by weight of an ethylene-methyl acrylate-maleic anhydride copolymer.
2. The covering material according to claim 1 , wherein the heat seal layer further comprises at least one selected from the group consisting of polyolefin-based resins, polyester-based resins, ethylene vinyl oxide, ethylene vinyl alcohol copolymer resins, and ethylene vinyl acetate copolymers.
3. The lid material according to claim 1, wherein the thickness of the substrate is 7 to 30 μm.
4. The amount of the heat seal layer laminated is 10 to 30 g / cm2 in terms of dry weight. 2 The lid material according to claim 1 .
5. The lid material according to any one of claims 1 to 4, which is used to heat-seal and seal a container having at least a glass opening by bringing the heat-seal layer into contact with the glass opening.
Citation Information
Patent Citations
JP1975005476A